2006
DOI: 10.1164/rccm.200509-1413oc
|View full text |Cite
|
Sign up to set email alerts
|

Novel Action of Indoleamine 2,3-Dioxygenase Attenuating Acute Lung Allograft Injury

Abstract: These results demonstrate that IDO prevents acute lung allograft injury through augmenting the local antioxidant defense system and inhibiting alloreactive T-cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 33 publications
5
107
0
2
Order By: Relevance
“…3,30 To verify co-gene delivery of FVIII and IDO can effectively express both proteins in vivo, hemophilia mice received a hydrodynamic injection containing equal amounts of the transposons pMSZ-CMV-FVIII and pMSZ-CMV-IDO (100 mg each), and 20 mg of transposase plasmid. Animals were killed 3 days or 4 weeks after gene delivery and transgene expression from liver tissue was analyzed by western blotting.…”
Section: Co-expression Of Fviii and Ido In Vivomentioning
confidence: 99%
See 3 more Smart Citations
“…3,30 To verify co-gene delivery of FVIII and IDO can effectively express both proteins in vivo, hemophilia mice received a hydrodynamic injection containing equal amounts of the transposons pMSZ-CMV-FVIII and pMSZ-CMV-IDO (100 mg each), and 20 mg of transposase plasmid. Animals were killed 3 days or 4 weeks after gene delivery and transgene expression from liver tissue was analyzed by western blotting.…”
Section: Co-expression Of Fviii and Ido In Vivomentioning
confidence: 99%
“…3,30 The hyperactive transposase expression plasmid (pCMV-HSB16) was used in these studies. 45 The ability of these plasmids to express biologically active protein was confirmed in vitro before the animal studies.…”
Section: Vector Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have also found that tryptophan catabolism prevents T cell-driven complement activation and inflammation during pregnancy (11), suggesting that IDO plays a key role in placenta immune privilege. IDOexpressing dendritic cells suppress allogeneic T cell proliferation in vitro by tryptophan metabolites (7) and IDO action attenuates allograft injury or rejection (12)(13)(14). Tryptophan catabolism also induces regulatory cells and is a means by which CTLA-4 signaling functions in vivo (15)(16)(17) while inhibiting IDO restores antitumor immunity (18).…”
Section: Suppression Of Memory Cd8 T Cell Generation Andmentioning
confidence: 99%